Promising crop biotechnologies for smallholder farmers in East Africa: bananas and maize: June 2006, briefs 19-26 - Smale, Melinda; Edmeades, S.; Groote, H. de (2006)
List of Briefs: 19. Assessing the Impact of Crop Genetic Improvement in Sub-Saharan Africa: Research Context and Highlights; 20. Crucial Determinants of Adoption: Planting Material Systems for Banana and Maize; 21. Gauging Potential Based on Current Adoption of Banana Hybrids in Tanzania; 22. Predicting Farmer Demand for Transgenic Cooking Bananas in Uganda; 23. Predicting Farmer Demand for Bt maize in Kenya; 24. Biodiversity of Bananas on Farms in Uganda; 25. Biodiversity of Maize on Farms in Kenya; 26. Biosafety and Biodiversity Risks.